The Model of Pathways to Treatment: Conceptualization and integration with existing theory. (27th April 2012) - Scott, S. E.; Walter, F. M.; Webster, A.; Sutton, S.; Emery, J.
<x xml:space="preserve">Abstract</x> Background. Studying and understanding pathways to diagnosis and treatment is vital for the development of successful interventions to encourage early detection, presentation, and diagnosis. An existing framework posited to describe the decisional and behavioural processes that occur prior to treatment (Andersen et al.'s General Model of Total Patient Delay) does not appear to match the complex and dynamic nature of the pathways into and through the health care system or provide a clear framework for research. Therefore a revised descriptive framework, the Model of Pathways to Treatment, has been proposed. Purpose. This paper presents the concepts and definitions of the Model of Pathways to Treatment and specifies how the model can encompass existing psychological theory, with particular focus on the Appraisal and Help‐seeking intervals. The potential and direction for future work is also discussed. Statement of contribution What is already known on this subject? The use of theory is often lacking in existing research into delays in presentation, diagnosis and treatment of illness. What does this study add? A detailed account of the concepts and definitions of a revised framework: the Model of Pathways to Treatment. Specification of how the Model of Pathways to Treatment can encompass existing psychological theory such as the Common Sense Model of Illness Self‐regulation and Social Cognitive Theory.